2007
DOI: 10.1007/s10526-007-9125-x
|View full text |Cite
|
Sign up to set email alerts
|

Intraguild predation involving Harmonia axyridis: a review of current knowledge and future perspectives

Abstract: 9 Abstract As an effective generalist predator of aphids and other hemipteran pests 10 H. axyridis has been a successful biological control agent. However, the very functional 11 traits that have contributed to its success in this regard also implicate it as an intraguild 12 predator that poses a significant risk not only to the diversity of other natural enemies of 13 Hemiptera (and their associated ecosystem services), but to biodiversity more widely. In 14 this paper we will specifically review the existing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(80 citation statements)
references
References 121 publications
1
78
0
1
Order By: Relevance
“…It has been demonstrated that H. axyridis is more aggressive than other invasive and indigenous species in many laboratory experiments (Hironori and Katsuhiro 1997;Cottrell and Yeargen 1998;Yasuda and Ohnuma 1999;Yasuda et al 2001;Cottrell 2004;Soares and Serpa 2007;Pell et al 2007;Ware and Majerus 2007). The incidence of IGP, in laboratory studies, was 65% for the interactions between all stages of H. axyridis (intraguild predator) and the indigenous C. maculata (intraguild prey), and 75% for H. axyridis and the invasive P. quatuordecimpunctata (Labrie et al unpublished data).…”
Section: Harmonia Axyridis: a Super Invader?mentioning
confidence: 98%
See 1 more Smart Citation
“…It has been demonstrated that H. axyridis is more aggressive than other invasive and indigenous species in many laboratory experiments (Hironori and Katsuhiro 1997;Cottrell and Yeargen 1998;Yasuda and Ohnuma 1999;Yasuda et al 2001;Cottrell 2004;Soares and Serpa 2007;Pell et al 2007;Ware and Majerus 2007). The incidence of IGP, in laboratory studies, was 65% for the interactions between all stages of H. axyridis (intraguild predator) and the indigenous C. maculata (intraguild prey), and 75% for H. axyridis and the invasive P. quatuordecimpunctata (Labrie et al unpublished data).…”
Section: Harmonia Axyridis: a Super Invader?mentioning
confidence: 98%
“…Harmonia axyridis is a highly efficient intraguild predator (Hironori and Katsuhiro 1997;Cottrell and Yeargen 1998;Yasuda and Ohnuma 1999;Yasuda et al 2001;Cottrell 2004;Soares and Serpa 2007;Pell et al 2007;Ware and Majerus 2007). However, eggs and first and second instar larvae are not well protected from other competitors.…”
Section: Harmonia Axyridis: a Super Invader?mentioning
confidence: 99%
“…Native ladybeetle populations have declined in most areas where H. axyridis has been introduced (Camacho-Cervantes et al, 2017) and this is often blamed on interference competition via intraguild predation (Pell et al, 2008). More specifically, H. axyridis is considered a top-level predator in the aphidophagous guilds, reflecting its direct predation behavior toward eggs and larvae of native coccinellids as well as non-coccinellid aphidophagous species, such as hoverflies and lacewing (Wells et al, 2017).…”
Section: Intraguild Predationmentioning
confidence: 99%
“…The arrival of H. axyridis is associated to drastic changes in coccinellid assemblages all around the word (Colunga-Garcia & Gage, 1998;Michaud, 2002;Lucas et al, 2007a,b;Pell et al, 2008;Bélanger & Lucas, 2011;Roy et al, 2012). Catalonia has a diverse agriculture dominated by winter cereals, maize, alfalfa, vegetables in open air and greenhouse, fruit orchards and vineyards.…”
Section: What Is the Phenology Of The Establishment And Spreading Of mentioning
confidence: 99%